PEMANFAATAN METODA JARINGAN SYARAF TIRUAN BACK PROPAGATION?ADA ANALISIS PENGARUH PARAMETER PEMOTONGAN TERHADAP KEMIRINGAN SISI POTONG HASIL PEMOTONGAN DENGAN LASER CO2 - Cahyati, Sally; Suroso, Suroso (MESIN, 2006)
The weakness of a laser cutting edges product is tapering form. Sometime tapering is an unwantedperformance product and needfinishing processes to eliminate its. Setting ofparameters cutting can minimizetapering. Amodeling of process is needed to represent the relationship influence of each parameter cutting.But there are difficulties torepresent them tobemathematical models. The solutionfor this case is use one ofArtificial Neural Network (ANN) method what is called Back Propagation. This is an appropriate method toprocess input - output data to be a model process. The results show that the tapering is significantlyinfluenced by the parameters process, the nozzle speed andgas pressure, having the most significant effects.